Otwarty świat i narracja rozproszona w grze Elden Ring studia FromSoftware - Maj, Krzysztof M. (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The article Open World and Dispersed Narrative in FromSoftware’s “Elden Ring” tackles a number of design issues associated with open world design in video games. Building upon Tim Ingold’s dis- crepancy of two distinct modes of exploring the reality (wayfaring and trail-following), the author proceeds with analysing how the categories in question might have influenced the design of Elden Ring’s ‘The Lands Between’, which is torn between two different ambitions. One is to create a high fantasy narrative in allotopia, whilst the other is to sustain the principles of procedural rhetoric typical for soulsborne games, well-known for leaning towards a dark fantasy design style both in terms of their aesthetics and narrative content. Consequently, the main goal of this analysis is to propose a potential way of avoiding such inconsequence in open world game design, which is termed here a “ludotopian dissonance”.